PENERAPAN BAHASA INGGRIS DENGAN METODE KREATIF PADA ANAK USIA DINI - Musdizal, Musdizal; Indrayadi, Toni; Fattia, Yandica Naila (Institut Agama Islam Negeri Kerinci, 2023)
Effective learning management requires various types of learning media. Learning media can accelerate students’ learning creativity and enable students to comprehend the concepts and content of the learning materials. Learning media are media in the teaching and learning process used to deliver material effectively from the teacher to the students. This research aims to examine creative crafting in early childhood. This research found that creative crafting media are very effective in improving children’s English competence. Creative crafting media develops children’s creativity, which could improve their motivation to learn and result in good learning outcomes. Thus, creative crafting media is a valuable learning medium to stimulate and support early childhood to improve their English competence and creativity.